Estudo numérico do uso de amortecedor magneto-reológico na redução de vibrações auto-excitadas durante torneamento - Camargo, Guilherme de (Universidade Federal de São Carlos, 2022)
Chatter are self-excited vibrations that may occur during machining operations. Despite being known for more than a century, chatter is still a major limiting factor on machining operations, decreasing productivity, tool life, and part quality. This paper reviews the chatter dynamics for the turning operation and propose the use of a magnetorheological (MR) damper to reduce the undesirable effects of chatter. The MR damper is characterized by the Modified Bouc-Wen model and the results are compared using the Stability Lobe Diagram (SLD). It is shown that the MR damper can effectively suppress chatter by increasing the Limiting Depth of Cut and, therefore, the material removal rate.
Numerical study of the use of magneto-rheological dampers for the reduction of self-excited vibrations during turning
Keywords: Diagrama de lóbulos de estabilidade; Amortecedor magneto-reológico; Stability lobe diagram; Magnetorheological damper; Chatter; ENGENHARIAS::ENGENHARIA MECANICA::MECANICA DOS SOLIDOS